2022
DOI: 10.29210/30032030000
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi program penyediaan perumahan pada masyarakat berpenghasilan rendah di kota Bukittinggi

Abstract: Penelitian ini bertujuan untuk mengidentifikasi penyediaan kebutuhan perumahan bagi masyarakat berpenghasilan rendah (MBR) di kota Bukittinggi, mengidentifikasi upaya yang dilakukan oleh masyarakat berpenghasilan rendah (MBR) di kota Bukittinggi dalam memenuhi kebutuhan perumahan, menganalisis hasil evaluasi program pemenuhan kebutuhan perumahan di masyarakat. berpenghasilan rendah (MBR) di Kota Bukittinggi. Metode yang digunakan adalah deskriptif kualitatif. Hasil penelitian ini menemukan bahwa program pembia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These variables include environmental economic resources that can support the successful implementation of policies; the extent to which interest groups provide support for policy implementation; characteristics of the participants, namely supporting or rejecting the nature of public opinion in the environment and whether the political elite supports policy implementation. Based on the results of research conducted by Prastiyo et al, (2022) the calculation of effectiveness found that the value of effectiveness, namely the program to fulfill housing needs that had been carried out was considered quite effective. Then, at the level of efficiency that is assessed in terms of house monitoring and assistance according to needs, it is considered quite efficient.…”
Section: Social Political and Economic Conditionsmentioning
confidence: 99%
“…These variables include environmental economic resources that can support the successful implementation of policies; the extent to which interest groups provide support for policy implementation; characteristics of the participants, namely supporting or rejecting the nature of public opinion in the environment and whether the political elite supports policy implementation. Based on the results of research conducted by Prastiyo et al, (2022) the calculation of effectiveness found that the value of effectiveness, namely the program to fulfill housing needs that had been carried out was considered quite effective. Then, at the level of efficiency that is assessed in terms of house monitoring and assistance according to needs, it is considered quite efficient.…”
Section: Social Political and Economic Conditionsmentioning
confidence: 99%
“…Introduction Every individual or group essentially wants to have a house that is livable, both in terms of physical and residential environment [7]. The continuing increase in population causes an imbalance between housing demand and housing supply, resulting in a housing shortage (Backlog).…”
mentioning
confidence: 99%